The Use of Buccal Fat Pad in the Treatment of Oral Submucous Fibrosis: A Newer Method - K. Saravanan; Vinod Narayanan (Hindawi Limited, 2012)
Purpose of the study. This study was to evaluate the use of buccal fat pad as an interpositioning material in surgical management of oral sub mucous fibrosis. Materials and methods. A series of 8 cases with proven oral sub mucous fibrosis, with mouth opening less than 20 mm, involving the buccal mucosa were treated surgically in the Department of Oral and Maxillofacial Surgery, College of Dental Surgery, Saveetha University, Chennai. Pedicled buccal fat pad was used as an interpositioning material to cover the raw areas in the oral cavity after incision and release of fibrous bands. Results. In 8 patients, the range of pre operative mouth opening was 3-18 mm (mean 14 mm). As the result of the successful surgical procedure, the size of the intra operative mouth opening was ranged from 25-38 mm (mean 33.25 mm). The patients were discharged 5-7 days after the operation. The range of the mouth opening at this time was 25-36 mm (mean 30.63 mm). The results were evaluated using student's t test and found to be statistically significant. The pedicled grafts took up uneventfull.